Analysis of the zoonotic tick-borne encephalitis virus (TBEV) in raw milk and dairy products in mountain pastures of the Lombardy region, Italy - Scarazzato, Annalisa; Righi, Francesco; Sommariva, Marco Pietro; Bertoletti, Irene; Sala, Giovanni; Paterlini, Franco; Daminelli, Paolo; Finazzi, Guido; Losio, Marina-Nadia; Pavoni, Enrico (Frontiers in Microbiology, 2024)
Over the last few decades, tick-borne encephalitis (TBE) has become a growing public health problem in Europe. The tick-borne encephalitis virus (TBEV) is a zoonotic virus that affects the Central Nervous System (CNS). TBEV has been detected in 27 European countries, and the rise in TBE cases is mainly due to environmental, ecological, and factors that increase the risk of human exposure to infected ticks. The infection via the alimentary route is the second most common means of TBEV transmission to humans. Raw milk from infected goats, sheep, or cows has been identified as a source of human food-borne infections. This study aims to gather new information on the prevalence of tick-borne encephalitis virus (TBEV) in raw goat's and cow's milk and related raw products in the Lombard Alps (Italy). This is important due to the close proximity of Lombardy to the Triveneto region, where TBE is endemic, and southern Switzerland, where numerous TBEVpositive mammals have been found. Throughout 2023, a passive monitoring plan was implemented on samples delivered for TBEV analyses from the Alpine pastures. Totally, 248 specimens including raw milk, raw milk cheese, and butter were tested. This is the first monitoring on food at risk of TBEV transmission in a non-endemic region with evidence of TBEV circulation. Despite testing a wide range of dairy products, no samples resulted positive for RNA-TBEV by real time RT-PCR. Preliminary results suggest that raw milk and raw dairy products do not pose a significant risk of TBEV transmission to humans in the territory of Lombardy.